The WHO healthcare standards in the context of demographic processes - Pabiś, Małgorzata; Kuncewicz, Dorota (Journal of Education, Health and Sport, 2018)
AimThe aim of the study was to analyze demographic changes in such a way as to provide data that might be useful for shaping the healthcare system in accordance with the WHO standards. The analysis was based on the example of the population over the age of 65.Materials and MethodsFocusing on the population over 65, we analysed statistics and demographic data using descriptive statistics methods. In addition, we referred to the demographic forecasts concerning the world population for 2020–2050.Results and ConclusionsWe juxtaposed the WHO standards with the size of the target group and the data which takes into account the difference in the age structure of the population in different regions of the world. Our conclusions cast doubt on the legitimacy of setting standards for the total population, both in terms of the current health care and future planning. Changes in the general population, and for example in the population over 65 are actually not proportional. Therefore, it seems more logical and reasonable to analyze data about geriatrics by examining the population over 65 only. The geriatric care base should be created using only and exclusively the data which concerns the group of patients to whom it is directed, namely elderly people.